Inovasi Dan Pengembangan Produk Stik Kangkung Di Desa Dasan Tereng Kabupaten Lombok Barat - Ni Wayan Sri Suliartini; Alfan Azizurohman; Made Aditya Budastra (Universitas Mataram, 2021)
Kangkong can be processed into various types of snacks, one of which is kangkong sticks. Sticks are a type of pastry that has a long flat shape, has a savory taste, and has a crunchy texture. Kangkong sticks are one form of innovation for processed kangkong products. Kangkong sticks were once produced in Dasan Tereng Village, but are no longer produced. Based on the results of interviews and observations conducted by the P1000WB Entrepreneurship Community Service Program (Creation of 1000 New Entrepreneurs), several problems have been found in the kangkong stick product. These problems include; unvaried taste, unattractive packaging, narrow marketing scope, and mass production system. KKN Kewirausahaan made various efforts to re-elevate, as well as develop kangkong stick products into superior products in Dasan Tereng Village. The efforts that have been made are: (1) Providing innovation in the form of flavor variants, (2) Improvement of product packaging using standing pouches, designing, and giving logos, (3) Doing digital marketing and changing the production system to a purchased order (PO) system. The method used is observation, short interview, and literature study. This gives tangible results in the form of product sales which are quite high, exceeding the sales target, from 40 packs to 110 packs in one week.